Impact of selective forwarding attack on AODV protocol in mobile wireless senor networks - Sehrawat, Harkesh; Singh, Yudhvir; Siwach, Vikas (International Journal of Engineering and Technology, 2018)
wireless sensor network is the growing field of research having capacity to help the mankind with its usage in varied areas like military surveillance, medical etc. However these networks are vulnerable to certain attacks like black hole, wormhole and selective forwarding. In this paper selective forwarding attack is analyzed on varying number of attacker nodes and its impact on different performance parameters. It is concluded that the performance of the entire network is degraded with the increase in the number of malicious nodes.Â Â